Pembangunan Sistem Pengelolaan Soal (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Abul A'la Alghifari; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Questions management is important process to be carried out in teaching and learning process, questions management is carried out by teacher, and with good questions management the teacher will be able to maintain the quality of the questions. At the Faculty of Computer Science Brawijaya University, questions management is carried out by lecturer team or commonly reffered to as team teaching. At present, the implementation of questions management that has been running has several problems, the first problem is the difficulty of gathering lecturers in one place at a same time. The second problem is the delay from the lecturer to collect the question that have been assigned. The third problem is the difference in the format of collected questions between one lecturer and another lecturer, that making it difficult for the team leader to combile the collected questions. Based on that problems, research was conducted which was intended to build a system that was able to facilitate the assignment distribution between lecturers, provide reminder to the lecturer about the assignment dependents, and facilitate the process of compiling and evaluating questions. This system is expected to be able to overcome existing problems and help improve the work efficiency of lecturers. This system has passed unit testing using whitebox testing, integration testing and validation testing using blackbox testing which results in a 100% valid value, and compatibility testing where the results of the system can run on eight different browsers.